Correction: Evaluation of synergistic effect of entomopathogenic fungi Beauveria bassiana and Lecanicillium lecacii on the mosquito Culex quinquefaciatus. - Aditya Shankar Kataki; Francesco Baldini; Anjana Singha Naorem (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0308707.].